Pengembangan Soal Higher Order Thinking Skills (HOTS) pada Materi Aljabar di Sekolah Menengah Pertama - Septiya Wulandari; Hajidin Hajidin; M Duskri (Universitas Syiah Kuala, 2020)
The Indonesian curriculum year 2013 requires students to have Higher Order Thinking Skills (HOTS) that match the competence needs in 21st century. Based on international assessment, Indonesias student rank is insufficient because the student is not familiar with solving problems requiring reasoning and analysis, including topic of algebra. This research aims to produce HOTS questions about algebra at Junior High School, which is valid, practical, and effective. This research is development research which consists of two stages, namely preliminary and formative evaluation. The participants in this study were grade 7 and 8 students in one Junior High School at Banda Aceh, Indonesia. The instruments were validation sheets, student response questionnaires, practicality test questionnaires, and HOTS questions. The result shows that the HOTS algebraic questions were meet the criteria: valid because all validators stated that the HOTS questions are suitable to use and the average value of the validation was reach very valid criteria; practical because all validators suggested that the learning tools can be applied in the class; effective because students response toward problems was positive dan the ability of students to solve questions is diverse. Thus, these HOTS questions can be used at the junior high school level.